Psikoanalisis Lacan dalam Novel Harapan di Atas Sajadah Karya Mawar Malka - Annisa, Suci Dwi; Shomary, Sudirman (UIR Press, 2024)
This research is motivated by literary works, which are a part of art that provides insights into human life. This study falls within the scope of psychoanalytic analysis, closely related to the personality of the characters in the novel. The aim of this research is to understand, analyze, and interpret the development of the characters' personalities in the novel